The Impact of Co-residence with Parents on Marital Satisfaction: Evidence from Indonesian Muslim Households - Okta Yutami; Erina Pane; Marwin Marwin (CV. Dyoqu Publishing and Management, 2025)
Background: In Indonesian Muslim communities, it is common for married couples to live with their parents or in-laws due to cultural traditions and economic factors. While this arrangement may provide support, it can also affect the quality of the marital relationship, especially in terms of privacy and emotional independence. Aims: This study aims to explore the impact of co-residence with parents or in-laws on marital satisfaction and compare it to couples who live independently in a rural Muslim setting. Methods: A qualitative field study was conducted in Pekon Rawas, Pesisir Barat, Indonesia. In-depth interviews were held with 20 Muslim couples—10 co-residing with parents or in-laws, and 10 living separately. Data were analyzed thematically to identify patterns related to relationship harmony, autonomy, and family involvement. Results: Couples who lived independently reported higher marital satisfaction, citing better emotional connection, greater privacy, and autonomy in decision-making. In contrast, co-residing couples experienced more tension due to frequent interference from parents or in-laws. Despite the challenges, no cases of marital separation were found. Conclusion: Living arrangements play a crucial role in shaping marital dynamics. Independent living tends to promote greater harmony and autonomy, while co-residence may pose risks to marital privacy and satisfaction. These findings offer insights for family counselors and policymakers working with traditional Muslim households.